2005
DOI: 10.1002/eat.20152
|View full text |Cite
|
Sign up to set email alerts
|

Bulimic symptoms, cognitions, and body dissatisfaction in women with major depressive disorder

Abstract: Eating disorder symptoms may be associated with depression in women in the absence of comorbid eating disorder diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…This correlation between a severe depressive symptomatology and ED severity validated the results of previous studies and confirmed expected hypothesis [2, 3, 30]. Moreover it is well known in literature that eating symptomatology is also associated with depression in women, even among those with no history of threshold-level eating disorder symptomatology [43]. …”
Section: Discussionsupporting
confidence: 89%
“…This correlation between a severe depressive symptomatology and ED severity validated the results of previous studies and confirmed expected hypothesis [2, 3, 30]. Moreover it is well known in literature that eating symptomatology is also associated with depression in women, even among those with no history of threshold-level eating disorder symptomatology [43]. …”
Section: Discussionsupporting
confidence: 89%
“…In addition to these sociocultural factors, there are also psychological dimensions that are robust correlates of disordered eating behaviors (Tylka and Subich 2004). Among young women, dysregulated eating behaviors are linked to depressive symptomatology in both clinical and non-clinical samples (Cooper et al 2005;Jackson et al 2003;Keel et al 2005;Troop et al 2001;Wildes et al 2005;Wonderlich and Mitchell 1997). Moreover, there is evidence of comorbidity with depression in patterns of both restrained and over-eating.…”
Section: Introductionmentioning
confidence: 97%
“…As psychic symptoms can influence the body image negatively [7,8], we supposed that there will be a negative correlation between psychic symptoms and body image, too.…”
Section: Methodsmentioning
confidence: 99%
“…The body image plays an important role in research on eating disorders [4], but during the last few years it has become relevant for other populations, too [5,6]. In some studies, relations between body concept and psychic disorders like depression or anxiety have been found [7,8]. …”
Section: Introductionmentioning
confidence: 99%